2008 IEEE International Multitopic Conference 2008
DOI: 10.1109/inmic.2008.4777715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nano particles on semiconductor manufacturing

Abstract: Semiconductor industry faces a continuous challenge to decrease the transistor size as well as to increase the yield by eliminating defect sources. One of the sources of particle defects is ultra pure water used in different production tools at different stages of processing. In this paper, particle count data measured in ultra pure water is related to the yield of two large size products. An impact of nano-particle present in ultra pure water on yield of up to 4-6 % has been found in two different products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Quantification of the particle concentration can be done by measuring the metal ion concentration, either in the solution or on the wafer surface with inductively coupled plasma-mass spectroscopy (ICP-MS). It was found that the scandium does not leach out of the particles even at pH 1 [47].…”
Section: Metal Ion Core Particlesmentioning
confidence: 96%
See 1 more Smart Citation
“…Quantification of the particle concentration can be done by measuring the metal ion concentration, either in the solution or on the wafer surface with inductively coupled plasma-mass spectroscopy (ICP-MS). It was found that the scandium does not leach out of the particles even at pH 1 [47].…”
Section: Metal Ion Core Particlesmentioning
confidence: 96%
“…Scandium was chosen because it is rarely used in the microelectronic environment (low background intervention) and this metal ion attaches very strongly to silica. The size of the particles is controlled by varying the reactant quantities [46]. Quantification of the particle concentration can be done by measuring the metal ion concentration, either in the solution or on the wafer surface with inductively coupled plasma-mass spectroscopy (ICP-MS).…”
Section: Metal Ion Core Particlesmentioning
confidence: 99%
“…Deviations in the device and material characteristics cause systematic yield loss. Contamination issues and process-induced particles are frequently linked to random defect yield loss [4]. The following are a few instances of contaminations and mechanisms responsible for the electronic chip failures in a semiconductor: particulate matter contamination, either from organic or inorganic matter particles created by the environment or by tools, and processes, such as scratches, fractures, overlay flaws, and stress [5].…”
Section: Introductionmentioning
confidence: 99%
“…As the design rule of the novel devices shrink to the nanometer scale, particle contamination is becoming more serious problem (1). These 'Killer' particles caused significant drop in production yield and delayed the ramping-up period for mass production of the new devices (2).…”
Section: Introductionmentioning
confidence: 99%